Undergraduates’ achievement and satisfaction: the role of study-related factors and soft skills - Sharabi, Adi; Carretti, Barbara; Cueli, Marisol; Rodríguez, Celestino; Pellegrino, Gerardo (Frontiers in Psychology, 2025)
The present study tested a comprehensive model in which five social, emotional, and behavioral (SEB) skill domains (self-management, social engagement, cooperation, emotional resilience, and innovation; also known as “soft skills”) were associated with academic achievement and satisfaction directly and through the mediation of academic self-efficacy and self-regulated learning (SRL) strategies. The participants were 319 undergraduate students (mean age = 22.74, SD = 4.68; 255 females) from Spain, Italy, and Israel. Self-report questionnaires were administered for this study. Our results showed that academic self-efficacy and SRL significantly mediated the relationships between self-management and social engagement skills with academic achievement, after controlling for sex, age, year of study, and nationality. Academic self-efficacy uniquely mediated the relationship between SEB skills and academic achievement and satisfaction. Fostering socio-emotional skills can benefit students during higher education and lead to positive perceptions of themselves as competent and self-regulated learners, which can lead to greater academic satisfaction and achievement.